Mengukur Readibility Bahan Ajar E-Learning dengan metode Cloze Procedure - Dani Indra Junaedi (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
To be understood by students, teaching materials must have a high level of readibility so measurements are needed before teaching materials are uploaded in the e-learning portal. Readability is used to describe language style factors in writing which make it easy to read. Readability is the total number of all elements and interactions between these elements, this affects the success of a printed item. Success in this case is seen from the level at which the reader understands (the paper), and is able to read it at the optimum speed, and in his opinion interesting. So that readability is considered as a reference to see the extent to which teaching material can be understood by readers. From the results of testing using the Cloze Procedure method conducted on writing e-learning teaching materials for Interpersonal Skill courses conducted by STMIK students as many as 50 people who have not taken the course show the average percentage of readibility for options without synonyms (% A ) at 60.25% and the synonym option considered correct (% B) at 65.4%. From these results it can be concluded that the e-learning teaching material on interpersonal skills courses is easy to read.